2018
DOI: 10.3892/ol.2018.7871
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CK19, CD105 and CD146 are associated with early metastasis in patients with renal cell carcinoma

Abstract: The present study was designed in order to explore the association between the early metastasis of renal cell carcinoma (RCC) and biological markers of tumor cells. A total of 200 patients with RCC, who received a nephrectomy between January 2015 and October 2015, were enrolled in the present study, while 100 healthy patients served as controls. The expression of cytokeratin 19 (CK19), endoglin (CD105) and cluster of differentiation 146 (CD146) were detected using immunohistochemical staining and western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
8
1
2
Order By: Relevance
“…It was revealed that the high CD105 copy number group survived for longer and this trend was in accordance with the in the high CD105 mRNA group. This appears in contrast with previous experimental results, where higher CD105 expression indicated more invasion and poor prognosis (20). Of note, previous studies also suggested that CD105 is an independent predictive marker for the risk of death and unfavourable prognosis in patients with ccRCC after curative resection (21,22).…”
Section: Discussioncontrasting
confidence: 99%
“…It was revealed that the high CD105 copy number group survived for longer and this trend was in accordance with the in the high CD105 mRNA group. This appears in contrast with previous experimental results, where higher CD105 expression indicated more invasion and poor prognosis (20). Of note, previous studies also suggested that CD105 is an independent predictive marker for the risk of death and unfavourable prognosis in patients with ccRCC after curative resection (21,22).…”
Section: Discussioncontrasting
confidence: 99%
“…Jakobiec et al (14) applied CK15 expression to investigate the property of the adenoma sebaceum, and Andruszkow et al (15) utilized CK19 expression for differential diagnosis of the basal cell carcinoma and adenoma sebaceum. Furthermore, it is reported that CK expression levels can be used to diagnose clear cell hidroadenoma (16) and primary neuroendocrine carcinoma (17) clinically, suggesting that detection of CKs may be beneficial to diagnosing epithelial tumor of the skin. In this study, comprehensive analyses on the experimental results were performed by virtue of the semi-quantitative scoring method via immunohistochemistry, and the findings were in line with partial results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In RCC cell lines CD105 www.nature.com/scientificreports www.nature.com/scientificreports/ was reported by us to be highly expressed in metastatic Caki-1 cell line before 12 , as well as by other groups 28 . Moreover, detection of CD105 marker in peripheral blood is considered to be effective tool to evaluate the early metastasis in RCC, especially in a cancer stem cell -positive conditions 30 . CD105 was shown to play functional role in maintaining cancer stem cell phenotype and epithelial -mesenchymal transition (EMT) phenotype 31 , while cells after EMT disseminate to distant organs and form metastases 32 .…”
Section: Discussionmentioning
confidence: 99%